فعالية تدريب الموارد البشرية في المؤسسات الصحية - سطايلي, محمد عبد المومن (My University, 2021)
This study aims at tackling a medium among media of the management of human resources since training plays a big role. The case concerns from one side a means to train and evaluate human capital, and from the other, a factor among the fundamental factors which helps the institution to face the economic, technological, organisational, social and cultural variations. In this framework, our study tries to show the effic iency of training programmes in achieving the objectives of the institution and thus it seeks to improve the performance in both economical and social fields. To achieve this aim, first a theoretical study of the role of training has been carried out, and then backing up this theoretical analysis through a practical field research about the training programmes of doctors epsp sidi lkhder. Concerning the results of the theoretical part, they have affirmed that the objectives of training process aim mostly at serving the institution objectives. As for the results of the questionnaire, they show the positive role of the programmes of training doctors in bettering .the quality of health services
المؤسسة العمومية للصحة الجوارية سيدي لخضر
Keywords: Human resources- the management of human resources-training-training programmes health institutions